Stability-and-Peace Accelerator for Food-Land and Water Systems Actors in Fragile and Conflict Affected Settings - Dahl, Hauke; Jacobs-Mata, Inga; Kamanda, Josey; Michalscheck, Mirja; Nkosi, Mahlatse (CGIAR System Organization, 2024)
The Stability-and-Peace Accelerator is a science-driven enterprise acceleration programme that identifies and enables the scaling of high-potential and high-impact innovations. These innovations promote the resilience of food, land and water systems (FLWS) in fragile and conflict affected settings (FCAs) in migrant and host communities. The accelerator programme aims to scale local innovations through science-based technical assistance and business development services by CGIAR researchers and partners, while assisting with demand-driven capacity building in humanitarian, development and peace settings facilitating investment opportunities for the identified private sector innovators through public/private finance actors. Ultimately, accelerator enables food and nutrition security, climate resilience, social cohesion and sustainability in emergency and humanitarian settings